Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Let ƒ(x) = 5x − 4 and g(x) = x2 - 1. Find (ƒ ○ g)(2).

Sagot :

(f ○g ) (2)= 11

Step-by-step explanation:

(f ○g ) (x)= (f(g(x))

= 5( x² -1) – 4

= 5x² – 5 – 4

= 5x² – 9

(f ○g ) (2)= (f(g(2)) = 5 (2)² – 9 = 5(4) – 9 = 20 – 9 = 11

I hope I helped you^_^

The resulting value of the composite function  is (ƒ ○ g)(2) is 11

Given the functions below

ƒ(x) = 5x − 4  

g(x) = x² - 1

Get the composite function (ƒ ○ g)(x)

(ƒ ○ g)(x) = f(g(x))

f(g(x)) = f( x^2 - 1)

f( x^2 - 1) = 5(x²-1)-4

f(g(x)) = 5(x²-1)-4

Substitute x = 2 into the expression to get (ƒ ○ g)(2).

(ƒ ○ g)(2)=  5(2²-1)-4

(ƒ ○ g)(2) = 5(3) - 4

(ƒ ○ g)(2) = 15 - 4

(ƒ ○ g)(2) = 11

Hence the resulting value of the composite function  is (ƒ ○ g)(2) is 11

Learn more here: https://brainly.com/question/8776301